Absolute Sea Level Changes Along the Coast of China From Tide Gauges, GNSS, and Satellite Altimetry. Issue 9 (9th September 2022) - Zhou, Dongxu; Liu, Yang; Feng, Yikai; Zhang, Huayi; Fu, Yanguang; Liu, Yanxiong; Tang, Qiuhua
Abstract: This study quantifies the absolute sea level (ASL) change along the coast of China from 1993 to 2019 using tide gauge (TG) and Global Navigation Satellite System (GNSS) data. The sea level change at 12 collocated TG and GNSS stations along the Chinese coast are first analyzed by TG + GNSS data. Then the ASL rise and its spatial variation along the coast of China and that in surrounding oceans are studied using TG + GNSS data and satellite altimetry products. The results show that the relative sea level rise along the Chinese coast varied from 2.61 ± 0.76 to 5.56 ± 0.70 mm/yr, while the effect of vertical land motion (VLM) ranged from −1.46 ± 0.30 to 1.07 ± 0.38 mm/yr. After correcting the effect of the VLM, the ASL rise ranged from 2.51 ± 0.86 to 5.03 ± 0.60 mm/yr, with a mean rate of 3.94 ± 0.88 mm/yr, which was 0.7 mm/yr higher than the global average. It is found that ASL rise rate is significantly higher in Chinese seas and neighboring oceans, with a meridional distribution in the East China Sea and a zonal distribution in the South China Sea. This may be related to factors such as sea surface temperature rise, atmospheric pressure decrease, freshwater runoff, zonal wind stress anomaly, and alongshore currents in the area. Plain Language Summary: As a consequence of climate change, the global mean sea level from tide gauges and satellite altimetry observations increased from 1.4 mm/yr over the period 1901–1990 to 3.2 mm/yr over the period 1993–2015 to 3.6 mm/yr over the period 2006–2015. An improved understanding of sea level rise is essential for the safety of society, the economy and the environment. This study quantifies the absolute sea level (ASL) change along the coast of China from 1993 to 2019 using tide gauge data with the vertical land motion corrected by Global Navigation Satellite System data. The derived ASL rise rate ranged from 2.51 ± 0.86 to 5.03 ± 0.60 mm/yr, with a mean rate of 3.94 ± 0.88 mm/yr, which was 0.7 mm/yr higher than the global average. It is also found that the ASL rise rate in Chinese seas and neighboring oceans is significantly higher than the global average, with a meridional distribution in the East China Sea and a zonal distribution in the South China Sea. The local influencing factors of sea level rise along the coast of China were analyzed, including the sea surface temperature rise, atmospheric pressure decrease, freshwater runoff, zonal wind stress anomaly and alongshore currents in the area. Key Points: Tide gauge and collocated Global Navigation Satellite System were first used to analyze the absolute sea level (ASL) changes along the coast of China The high ASL rise rate along the Chinese coast was a natural manifestation in all Chinese seas and neighboring oceans The local influencing factors of sea level rise along the coast of China were preliminarily analyzed